Stabilized landfill leachate treatment by combined physicochemical–nanofiltration processes - Trebouet, D; Schlumpf, J.P; Jaouen, P; Quemeneur, F (Water research (Oxford), 2001)
Landfill leachate is a complex wastewater which the composition and concentration of contaminants are influenced by the type of waste deposited and the age of landfill. In the last years, several processes or process combinations were developed and tested to reach requirements for the discharge of leachate. Among the new processes, membrane processes are considered as promising: reverse osmosis is one of the most widely used treatment in the Northwestern European countries and nanofiltration is gained in popularity during the last 5 years. Successful application of membrane technology for the treatment of landfill leachates, requires efficient control of membrane fouling. Two organic membranes of nanofiltration were used for pilot-scale testing. Leachates were subject to several pretreatments (pH modification, prefiltration and coagulation with FeCl 3) to remove potential foulants including dissolved organic and inorganic substances, colloidal and suspended particles. These pretreatments do not enhance the performances (retention and permeation flux) of membranes because the pH range and the presence of Fe 3+ ions contribute greatly to change the characteristics of organic matter and the surface charges of membranes. However, the results show that nanofiltration is sufficient to eliminate refractory COD, the permeates have a COD lower than the requirements for discharge.